PENERAPAN TEORI PERLINDUNGAN HUKUM TERHADAP HAK CIPTA ATAS PENYIARAN - Annisa Justisia Tirtakoesoemah; Muhammad Rusli Arafat (Faculty of Law, Universitas Pekalongan, 2019)
Intellectual property rights by nature provide economic benefits to the creator or holder of copyright and also to the state. Among the European countries that are members of the Euroean Union (EU) and in America, this awareness of economic benefits has been firmly planted. In these developed countries, several economic studies have been conducted which have proven the rapid growth of copyright contribution to the national income of the country. The need to recognize, protect and reward individuals or companies for their inventions and access to their work for the benefit of humans is beginning to be felt in Indonesia. In the context of copyright ownership over anything related to intellectual property rights, the law acts and guarantees the creator to control and enjoy exclusively the results of his work and if necessary with the assistance of the state for law enforcement. The results showed that legal protection can be carried out with supervision by the government and involves legal entities that already have the authority, socializing both the creators of a work or the copyright holder of a related rights product on the importance of registering or recording the work and the copyright holder submits lawsuit to the Commercial Court.Keywords:Legal Protection, Intellectual Property Rights, Copyright, Legal Entity